MODELLING OF INDUCTION MOTOR WITH ANSYS MAXWELL RMXPRT PROGRAMM (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2026)
The article illustrated the design and modeling of an asynchronous electric motor by using the program Ansys Maxwell. Ansys Maxwell RMxprt is used in order to demonstrate the result of design and modeling of electrical machines. The advantages of using the program module Ansys Maxwell RMxprt for the design of electrical machines are revealed and the results of the analysis of their performance are showed. The results of the calculation of the operating characteristics are given in the data tables and in the form of graphical characteristics.
Keywords: asynchronous electric motor, stator, rotor, Ansys Maxwell RMxprt, performance characteristics, net power, power factor, efficiency.